Intravascular vs. surface cooling in out-of-hospital cardiac arrest patients receiving hypothermia after hospital arrival: a post hoc analysis of the TTM2 trial - Awad, Akil; Jonsson, Martin; Holgersson, Johan; Jakobsen, Janus Christian; Hollenberg, Jacob; Thomas, Matthew; Garcia, Pedro D Wendel; Ringh, Mattias; Grejs, Anders M; Keeble, Thomas R; Bělohlávek, Jan; Cariou, Alain; et al. (Intensive care medicine, 2025)
PURPOSE: To compare the performance of targeted temperature management (TTM) at 33 °C using intravascular (IC) vs. surface-cooling (SFC) devices after out-of-hospital cardiac arrest (OHCA). METHODS: A post hoc analysis including OHCA patients randomized to hypothermia in the TTM2-trial (NCT02908308) comparing hypothermia with normothermia. The main outcome was cooling performance, defined as the proportion of patients reaching target temperature < 33.5 °C within 4 h, time outside temperature ranges during maintenance, rewarming rate and post-TTM fever. Exploratory outcomes included survival and good functional outcome, defined as modified Rankin Scale (mRS) scores of 0-3 at 6 months, analyzed using Inverse Probability Treatment Weighting (IPTW). RESULTS: Among 930 patients randomized to hypothermia, 876 were treated with a cooling device and included in this study. Of those, 27.3% received IC devices, while 72.7% received SFC devices. The proportion reaching target temperature within 4 h was higher with IC (IC: 69.6% vs. SFC: 49.2%; p < 0.001). Temperature outside ranges during the cooling period and post-TTM fever were lower with IC compared to SFC (17.2% vs. 39.6%; p < 0.001 and 0% vs. 6.3%; p < 0.001, respectively). In the exploratory IPTW analysis, 6-month survival rates were 55.2% in the IC group and 50.2% in the SFC group (OR 1.22, 95% CI 0.89-1.68) and survival with good functional outcome at 6 months was 51.1% patients in the IC group and 44.9% in the SFC (OR 1.28, 95% CI 0.93-1.77). CONCLUSIONS: Among OHCA patients randomized to hypothermia in the TTM2 study, intravascular cooling, compared with surface cooling, was associated with better cooling performance.
Keywords: Out-of-hospital cardiac arrest; Humans; lidé středního věku; Hypothermia, Induced; Cardiopulmonary Resuscitation; Female; Aged; výsledek terapie; senioři; lidé; kardiopulmonální resuscitace; ženské pohlaví; Male; Middle Aged; Treatment Outcome; Surface cooling; Hypothermia; Intravascular cooling; zástava srdce mimo nemocnici; Out-of-Hospital Cardiac Arrest; mužské pohlaví; terapeutická hypotermie